PENGARUH WORK-LIFE BALANCE TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. COLOMBUS PALOPO - Wiwik Wiwik; Junita Pabunta; Yuspita Yuspita; Ratna Tukan; Khaerana Khaerana; Erwina Erwina (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research reveals the main problems relating to employee performance. Thus, this research aims to determine the effect of work life balance on employee performance at PT. Columbus, Palopo city. This research is correlational with a quantitative approach applied using statistical formulas to assist in analyzing the data and facts obtained. The population in this study were all employees at PT. Columbus in the city of Palopo as many as 38 people. The sample in this research is employees at PT. Colombus, Palopo city, as many as 38 people were taken using saturated sampling. Data collection uses a questionnaire. Data analysis uses simple linear regression analysis. The results of the research show that there is a significant influence between the influence of work life balance on employee performance at PT. Columbus, Palopo city, where the significance value is 0.001 <0.05. Work life balance and job satisfaction contribute to respondents' performance, so they can be used as benchmarks for improving employee performance.